A cross-sectional study on the cardiac imaging methods including electrocardiograms and echocardiography of the heart in patients with COPD - M. S., Rohan; R., Umashankar; Ramineni, Saketh (International Journal of Research in Medical Sciences, 2025)
Background: This study aimed to analyze electrocardiographic (ECG) and echocardiographic changes in patients with Chronic Obstructive Pulmonary Disease (COPD) and to correlate these findings with disease severity and duration. It also compared the diagnostic utility of clinical evaluation, ECG and echocardiography in detecting right ventricular (RV) dysfunction. Methods: A cross-sectional observational study was conducted over one year in the medical wards of Sree Balaji Medical College and Hospital, Chennai. Fifty patients with clinically and spirometrically confirmed COPD were included using systematic random sampling. Detailed clinical history, including smoking habits and symptom duration, was recorded. All patients underwent spirometry, ECG and echocardiography. Disease severity was graded using the British Thoracic Society (BTS) criteria. Data were analyzed using Pearson’s correlation and Chi-square tests, with p <0.05 considered statistically significant. Results: The mean age of the study population was 59.9±10.4 years, with a male predominance. The average disease duration was 5.71 years and mean smoking exposure was 23.2±3.6 pack-years. Severe COPD (FEV₁ < 40%) was common. ECG findings such as P pulmonale, right axis deviation, right bundle branch block, right ventricular hypertrophy and poor R-wave progression were associated with disease severity. Echocardiographic abnormalities included RV dilation, hypertrophy, pulmonary hypertension and cor pulmonale. Cor pulmonale was clinically evident in 36%, detected by ECG in 44% and confirmed by echocardiography in 54% of cases. Conclusions: ECG and echocardiography serve as valuable tools for detecting RV dysfunction in COPD, with echocardiography demonstrating superior sensitivity.